Access to α, α-difluoro(arylthio)methyl oxetanes from α, α-difluoro(arylthio)methyl ketones and trimethylsulfoxonium halides: scope, mechanism and applications. Issue 7 (2nd February 2022) - Cai, Yingying; Liu, Chi; Liu, Guangying; Li, Chengxi; Jiang, Huanfeng; Zhu, Chuanle
Abstract : A general and practical method to access α, α-difluoro(thio)methyl oxetanes via the coupling of α, α-difluoro(thio)methyl ketones with trimethylsulfoxonium halides is reported. Abstract : A general and practical method for the synthesis of α, α-difluoro(arylthio)methyl oxetanes that occurs by the reaction of α, α-difluoro(arylthio)methyl ketones with trimethylsulfoxonium halides is reported. This reaction proceeds via the sequential Corey–Chaykovsky epoxidation and regioselective ring-expansion pathways and features mild conditions, operational simplicity, gram-scalability, a broad substrate scope and high yields. α, α-Difluoro(arylthio)methyl oxiranes have been shown to be the reaction intermediates. The obtained α, α-difluoro(arylthio)methyl oxetanes were further converted into useful sulfone, butenolide, and tetrahydrofuran derivatives.